Developing powerful athletes, Part 1: Mechanical underpinnings. - Turner, A. N.; Comfort, P.; McMahon, J.; Bishop, C.; Chavda, S.; Read, P.; Mundy, P.; Lake, J. (Strength and Conditioning Journal, 2020)
This review will revisit practitioner understanding of the development of power, before outlining some of the key mechanical parameters that contribute to power development. This understanding will help with planning and periodization of strength and power training, which is explored in part 2 of this 2-part review. This review (part 1) discusses the force-time and force-velocity curve and addresses recent criticism in using terms such as power, rate of force development, and explosiveness, over impulse. These terms are distinguished mechanically and conceptually for the benefit of the scientist and coach, and are essential for effective sharing of data and practice.